2013
DOI: 10.1016/j.comptc.2012.08.018
|View full text |Cite
|
Sign up to set email alerts
|

The second-order reduced density matrix method and the two-dimensional Hubbard model

Abstract: The second-order reduced density matrix method (the RDM method) has performed well in determining energies and properties of atomic and molecular systems, achieving coupled-cluster singles and doubles with perturbative triples (CCSD(T)) accuracy without using the wave-function.One question that arises is how well does the RDM method perform with the same conditions that result in CCSD(T) accuracy in the strong correlation limit. The simplest and a theoretically important model for strongly correlated electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 55 publications
1
36
0
Order By: Relevance
“…For consistency the symmetry then has to be enforced in these blocks by imposing linear constraints on the 2DM during the optimization. [39], and it is shown that they correspond.…”
Section: Point Group Symmetrymentioning
confidence: 91%
“…For consistency the symmetry then has to be enforced in these blocks by imposing linear constraints on the 2DM during the optimization. [39], and it is shown that they correspond.…”
Section: Point Group Symmetrymentioning
confidence: 91%
“…As a consequence, the two less stringent conditions T 1 and T 2 , originally proposed by Erdahl [52], and implemented for small atoms and molecules by Zhao et al [22] are used in practical calculations. They read: (24) which are both positive semidefinite. The fundamental interest of Eqs.…”
Section: B N-representability Conditions and Many-body Quantum Numbersmentioning
confidence: 99%
“…These conditions consist in positive semidefinite operators, whose expectation value thus has to be non-negative when evaluated with a 2RDM. Moreover, they can be systematically arranged in a hierarchy where each level yields an increasingly tighter lower bound on the exact ground-state energy [15,16,18,[23][24][25]. However, limitations in optimization software and computer resources prevented the practical development of the 2RDM method for several years.…”
Section: Introductionmentioning
confidence: 99%
“…(1) was unknown until recently, 8 an approximate class of Nrepresentability constraints has been demonstrated to be sufficient for calculating ground-state properties of the metal-to-insulator transition of hydrogen chains, 9 ground states and charge distributions of quantum dots, 10 quantum phase transitions, 11,12 dissociation channels, 13 and quantum lattice systems. [14][15][16][17][18][19][20] Variational minimization of the energy as a functional of the 2-RDM is expressible as a special convex optimization problem known as a semidefinite program.…”
Section: Introductionmentioning
confidence: 99%
“…While recent RDM calculations have examined linear 14 as well as 4 × 4 and 6 × 6 Hubbard lattices, 15,20 there has not been an exploration of RDMs on quasi-one-dimensional Hubbard lattices with a comparison to the one-dimensional Hubbard lattices. How does the electron correlation change as we move from a one-dimensional to a quasi-one-dimensional Hubbard model?…”
mentioning
confidence: 99%